Analysis of Indihome Provider Marketing Mix Factors on Consumer Subscription Satisfaction - Mada Shinta Dewi (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
It is the purpose of this study to examine the elements that influence consumer subscription satisfaction at PT Telkom Indonesia Karawang in terms of the marketing mix, which includes product, price, promotion, and place provider Indihome. The quantitative analytical method was employed in this investigation. The technique of creating a scale utilizing the Likert scale technique was used in this investigation. The researcher employed multiple regression analysis to analyze the data collected during the study. The sample size for this study was 50 people that took part in it. The findings revealed that product, price, promotion, and location all had an impact on consumer satisfaction with the Indihome provider at PT Telkom Indonesia Karawang in a partial and simultaneous manner. The researchers also discovered that the four independent factors had a combined influence on the fixed variable, which was customer satisfaction, of 76.6 percent.